PENGGUNAAN METODE CIRC UNTUK PENINGKATAN KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI PUNCAKMANGGU: Penelitian Tindakan Kelas - Nurfalah, Nurfalah; Rifky Aditya Ramadhan; Efi Kurniasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to improve students' writing skills in the Indonesian Language subject through the implementation of the Cooperative Integrated Reading and Composition (CIRC) method at SD Negeri Puncakmanggu. The background of this study is the low level of students' writing skills, which is caused by conventional teaching practices, limited variation in instructional methods, and the lack of attractive and interactive learning media. The Cooperative Integrated Reading and Composition (CIRC) method was chosen because it emphasizes group cooperation, integrates reading and writing activities, and can enhance students' motivation and understanding. This study employed a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of the study were students of SD Negeri Puncakmanggu. Data collection techniques included writing skill tests, observations of student and teacher activities, and documentation. The data were analyzed using descriptive qualitative and quantitative methods to determine the improvement in students' writing skills after the implementation of the Cooperative Integrated Reading and Composition (CIRC) method. The results of the study showed that the implementation of the Cooperative Integrated Reading and Composition (CIRC) method significantly improved students' writing skills. This improvement was indicated by the increase in the average writing skill scores, greater student participation during the learning process, and enhanced ability of students to express their ideas in written form in a more structured and creative manner. Therefore, the use of the Cooperative Integrated Reading and Composition (CIRC) method is effective in improving writing skills in the Indonesian Language subject at SD Negeri Puncakmanggu. Keywords: Cooperative Integrated Reading and Composition (CIRC), writing skills, Indonesian Language, elementary school.